Popelka a další pohádky - Hons, Václav, 1938-; Tušl, Jiří, 1943-; Suchý, Ondřej, 1945-; Kašpárková, Marcela, 1962-; Říha, Bohumil, 1907-1987; Andersen, Hans Christian, 1805-1875; Horčička, Jiří, 1927-2007; Šafránková, Libuše, 1953-2021; Trávníček, Pavel, 1950-; Hlaváčová, Jana, 1938-2024; Preissová, Jana, 1948-; Munzar, Luděk, 1933-2019; et al. (Supraphon, 2018)
Dvě varianty pohádky o Popelce a další dvě známé pohádky v podání předních čerkých herců.